Dynamic tax evasion and growth with heterogeneous agents - Francesco Menoncin; Andrea Modena (Journal of Economic Interaction and Coordination, 2024)
We develop a tractable model economy in which public capital improves aggregate productivity, and the taxpayers have heterogeneous evasion opportunities. By issuing bonds, compliant taxpayers supply the evaders with an instrument to hedge against auditing risks, thereby expanding their evasion capacity. The wealth share of tax evaders relates negatively to the economy's productivity but has a hump-shaped relationship with the growth rate of aggregate capital. The fiscal policy that maximizes welfare differs from the one that maximizes tax revenues because the latter does not account for the redistribution of wealth (and risk) between compliant and evasive taxpayers.
Keywords: E20; G11; H26; 330; Dynamic tax evasion; General equilibrium; Growth; Heterogeneous agents